1996
DOI: 10.1111/j.1745-4557.1996.tb00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Physical‐chemical Composition of Raw Peas and Sensory Attributes of Canned Peas

Abstract: Two pea cultivars (Citrina and Warindo) at four commercial sizes (superfine, very-fine, fine and middle) were selected for a study of their physicalchemical parameters of raw and sensory attributes after canning. To determine the relationships between the physical-chemical parameters and the sensory attributes, Principal Component Analysis (PCA) was applied. About 65 % of the total variation in the physical-chemical parameters and sensory attributes was expressed by two PCA Factors. Mealiness was an important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
(8 reference statements)
2
8
0
1
Order By: Relevance
“…All years gave almost similar results. Our data support results of Martens (1986) and Periago et al (1996), who reported that TV, AIS and dry weight and sensory mealiness and juiciness describe one dimension of pea quality.…”
Section: Relationship Between Chemical-physical and Sensory Measurementssupporting
confidence: 95%
“…All years gave almost similar results. Our data support results of Martens (1986) and Periago et al (1996), who reported that TV, AIS and dry weight and sensory mealiness and juiciness describe one dimension of pea quality.…”
Section: Relationship Between Chemical-physical and Sensory Measurementssupporting
confidence: 95%
“…In general, soluble, insoluble and total NSP, cellulose and uronic acids decrease with seed development. We have reported (21) an increase of NSP content in peas after cooking, which is due to losses of non-fibre material, presumably mainly free sugars. The losses of other nutrients was higher in Citrina SF size than in Warindo SF size, since the former was less mature (22).…”
Section: Resultsmentioning
confidence: 96%
“…Crispness, juiciness as well as bitterness, sweetness and fruity flavor were found to be the most important quality criteria describing the sensory quality of vegetables (carrots, swedes and cauliflower) (Fjeldsenden et al 1981). In other studies (Martens 1986;Periago et al 1996) undertaken to assess the sensory, chemical and physical criteria of frozen peas and canned peas (evaluated as warm peas) mealiness, hardness, fruity flavor and sweetness were found to be the most relevant in determining sensory quality. Advantages of evaluating cold peas are that it allows a more simple sample preparation, is more robust in relation to the effects of temperature and time, and needs fewer resources in general than for evaluation of warm peas.…”
Section: Introductionmentioning
confidence: 99%